Tibiocalcaneal arthrodesis in fixed equinus deformity with ring fixator: functional assessment and quality of life - Souza, Rafael Bispo de; Pereira, Antônio Carlos Faloni Nunes; Nerys, Rafael Costa; Martins, Jefferson Soares; Costa, Edegmar Nunes (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate the limb function and quality of life of patients with posttraumatic fixed equinus deformity treated at a tertiary hospital after arthrodesis with the Ilizarov external fixator. Methods: A study was conducted from January 2015 to June 2018 in which 6 patients were evaluated at outpatient follow-up in the late postoperative period. First, an identification questionnaire was administered to assess limb function using the American Orthopedic Foot and Ankle Society (AOFAS) scale, and quality of life was assessed using the SF-36 questionnaire. Results: A total of 66.6% of the sample had an AOFAS score below 70 (mean total = 57.5), which is considered poor. The mean SF-36 score was low (below 60) in all domains evaluated. The pain domain had the highest score (mean = 57.2). Conclusions: Even after surgery to correct the deformity, patients had impaired function and quality of life. Level of Evidence IV; Therapeutic Studies; Case Series.